Persistently active, pacemaker-like neurons in neocortex - Le Bon-Jego, Morgane; Yuste, Rafael (Frontiers in Neuroscience, 2007)
The neocortex is spontaneously active, however, the origin of this self-generated, patterned activity remains unknown. To detect potential "pacemaker cells," we use calcium imaging to directly identify neurons that discharge action potentials in the absence of synaptic transmissionin slices from juvenile mouse visual cortex. We characterize 60 of these neurons electrophysiologically and morphologically, finding that they belong to two classes of cells: one class composed of pyramidal neurons with a thin apical dendritic tree and a second class composed of ascending axon interneurons (Martinotti cells) located in layer 5. In both types of neurons, persistent sodium currents are necessary for the generation of the spontaneous activity. Our data demonstrate that subtypes of neocortical neurons have intrinsic mechanisms to generate persistent activity. Like in central pattern generators (CPGs), these neurons may act as "pacemakers" to initiate or pattern spontaneous activity in the neocortex.